Myosin 1b Participated in the Modulation of Hypoxia/Reoxygenation-Caused H9c2 Cell Apoptosis and Autophagy - Jing Xu; Jin Huang; Xiaojie He; Mingshuang Hu; Shan Su; Ping Liu (Analytical Cellular Pathology)
Myocardial ischemia/reperfusion (I/R) injury seriously threats the health and life of patients with ischemia heart disease. Herein, we probed the potential influence of myosin 1b (myo1b) on hypoxia/reoxygenation- (H/R-) stimulated cardiomyocyte H9c2 cell apoptosis and autophagy. After H/R stimulation, the myo1b mRNA level in H9c2 cells was tested via qRT-PCR. Myo1b overexpression plasmid (OE-myo1b) and small interfering RNA (siRNA) targeting myo1b (si-myo1b) were transfected into H9c2 cells to alter myo1b expression in H9c2 cells. Following H/R stimulation and/or OE-myo1b (or si-myo1b) transfection, H9c2 cell apoptosis, proliferation, and autophagy were detected, respectively. We found that H/R stimulation reduced the mRNA level of myo1b in H9c2 cells and resulted in H9c2 cell apoptosis, proliferation inhibition, and autophagy. Overexpression of myo1b reversed the H/R-resulted H9c2 cell apoptosis, proliferation inhibition, and autophagy. Silence of myo1b had opposite effects, which promoted H9c2 cell apoptosis, reduced cell proliferation, and accelerated cell autophagy. Taken together, Myo1b took part in the modulation of H/R-stimulated cardiomyocyte apoptosis and autophagy, which might be serve as a potential endogenous target for prevention and therapy of I/R injury.